486 QUANTIFYING WYOMING'S PRIMARY CARE PHYSICIAN SHORTAGE. Issue 1 (1st January 2007) - Corson, D. G.; Norris, T.
Abstract : Background: This study assessed the primary care physician shortage relative to population in Wyoming based on comparison with national levels of primary care physicians. Study Design and Methods: All primary care (family practice, general internal medicine, and pediatric) physicians practicing in Wyoming, or their office managers, were interviewed by telephone. Physicians/office managers identified the county the physician practiced in, physician's specialty, and average weekly hours each physician offered direct patient care in the clinic (ambulatory care). Thirty-four hours of ambulatory care provided per week were defined as one full-time equivalent (FTE). Total FTEs for the three specialties were calculated for each of Wyoming's 23 counties by dividing the number of ambulatory hours per county per week by 34. "Expected" weekly FTEs were calculated by dividing each county's population by the national population-to-physician ratio of the three respective specialties. Using 2005 AMA masterfile data, these ratios were identified as 1, 985.07 to 1 in family practice, 1, 817.21 to 1 in internal medicine, and 3, 385.49 to 1 in pediatrics. FTE shortage was calculated by subtracting the expected weekly FTEs for each county from the number of actual weekly FTEs. Results: Wyoming's total primary care FTEs comprised only 37.83% of expected primary care FTEs. This indicated a total shortage of 426.13 ambulatory primary care FTEs each week. Nineteen of 23 counties showed family-practice FTE shortages. Statewide family practice FTEs were 76.14% of the expected FTEs with a shortage of 103.19 ambulatory family practice FTEs each week. All 23 counties showed internal medicine FTE shortages. Statewide internal medicine FTEs were 20.42% of the expected internal medicine FTEs, with a shortage of 207.73 internal medicine FTEs each week. AllAllAll 23 counties showed pediatric FTE shortages. Statewide pediatric FTEs were 17.84% of the expected pediatric FTEs, with a shortage of 115.2 pediatric FTEs each week. Conclusion: There is a major shortage of family practice, general internal medicine, and pediatric physicians across Wyoming. Wyoming must consider the implications of this shortage on the current and future health care needs of its citizens.